Potensi pengembangan pariwisata berkelanjutan pada museum universitas - Riyani, Nurkhasanah Eka; Tanudirdjo, Daud Aris (Universitas Negeri Malang, 2024)
Abstract Museums has an important role to play in the Sustainable Development Goals (SDGs) agenda. Among the many types of museums, university museums have the most potential to play this role. The management of university museums under higher education institutions allows easier access to developments in science and technology including various research and innovations that respond to sustainable development goals. This research aims to examine the potential for developing a sustainable tourism model in the campus environment by university museums with a case study of cultural heritage tour activities at Gadjah Mada University campus. This research is a qualitative research that will be analyzed through potential analysis. The result is that there are several locations in the UGM campus environment that can be used as tourist destinations by carrying out the concept of sustainability as an effort to educate the importance of public awareness of sustainable development.Abstrak Bidang permuseuman memiliki peran penting dalam agenda pembangunan berkelanjutan atau Sustainable Development Goals (SDGs). Di antara banyak jenis museum, museum universitas memiliki potensi yang paling unggul dalam menjalankan peran ini. Pengelolaan museum universitas di bawah institusi perguruan tinggi memungkinkan akses yang lebih mudah terhadap perkembangan ilmu pengetahuan dan teknologi termasuk di dalamnya berbagai penelitian dan inovasi yang merespons tujuan pembangunan berkelanjutan. Penelitian ini bertujuan untuk mengkaji potensi pengembangan model pariwisata berkelanjutan di lingkungan kampus oleh museum universitas dengan studi kasus kegiatan tur warisan budaya kampus Universitas Gadjah Mada. Penelitian ini merupakan penelitian kualitatif yang akan dianalisis melalui analisis potensi. Hasilnya terdapat beberapa lokasi di lingkungan kampus UGM yang dapat dijadikan destinasi wisata dengan mengusung konsep keberlanjutan sebagai upaya edukasi pentingnya kesadaran publik terhadap pembangunan berkelanjutan.